2017
DOI: 10.1016/j.mayocp.2017.06.022
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis and Management of Bipolar I and II Disorders: Clinical Practice Update

Abstract: Bipolar disorders, including bipolar I disorder (BP-I) and bipolar II disorder (BP-II), are common, potentially disabling, and, in some cases, life-threatening conditions. Bipolar disorders are characterized by alternating episodes of mania or hypomania and depression, or mixtures of manic and depressive features. Bipolar disorders present many diagnostic and therapeutic challenges for busy clinicians. Adequate management of bipolar disorders requires pharmacotherapy and psychosocial interventions targeted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 149 publications
0
40
0
13
Order By: Relevance
“…BD is not just one disorder but several, with the age at onset typically being late adolescence into young adulthood [66][67][68][69][70][71]. BP-I (Bipolar I) is characterized by episodes of mania.…”
Section: Bipolar Disorders (Bd) Including Prevalence and Burden Of Ilmentioning
confidence: 99%
“…BD is not just one disorder but several, with the age at onset typically being late adolescence into young adulthood [66][67][68][69][70][71]. BP-I (Bipolar I) is characterized by episodes of mania.…”
Section: Bipolar Disorders (Bd) Including Prevalence and Burden Of Ilmentioning
confidence: 99%
“…10,11 BD is a serious psychiatric illness, defined by recurrent depressive, manic and mixed episodes, separated by periods of clinical remission, with an estimated lifetime prevalence of 3-7%. 12,13 In a large community sample, the prevalence of BD in women with PMDD was about 10%, seven-times higher than what observed in those without PMDD. 14 A systematic review conducted in 2014 reported that 15-27% of women with BD met an adjunctive diagnosis of PMDD, supporting the hypothesis that a subgroup of BD may have a hormonal sensitivity.…”
Section: Introductionmentioning
confidence: 90%
“…One important and recent development in the area of mood disorders is the recognition that many patients initially suspected suffering from major depressive disorder suffer instead from a form of bipolar disorder (BD) [1]. Symptomatic bipolar disorder patients are more frequently in the depressive condition rather than in hypomanic, manic, or mixed states [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…One important and recent development in the area of mood disorders is the recognition that many patients initially suspected suffering from major depressive disorder suffer instead from a form of bipolar disorder (BD) [1]. Symptomatic bipolar disorder patients are more frequently in the depressive condition rather than in hypomanic, manic, or mixed states [1][2][3]. As a consequence, such patients can be improperly diagnosed as suffering from major depression and prescribed antidepressants instead of the lithium, atypical antipsychotics, or antiepileptic-type mood stabilizers normally used to treat bipolar spectrum disorders [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation